The Phenomenon Of Homelessness And The Psychosocial Problems Of The Homeless - Elif Civan Yüce; Seda Kuzgun; Hüseyin Zahid Kara; Yusuf Genç; Fatmanur Alsancak (Sakarya University Journal of Education)
This study focuses on the case of homelessness in different countries and how the specific characteristics of homeless people differ in these countries. The data of the research based on the field survey were obtained via questionnaire form from the homeless living in Hungary, Italy, Austria and Turkey. According to the findings, homeless people started drinking between 0-17 years of age, higher in Italy, Hungary and Austria, while lower in Turkey. Again, the experience of divorce before homelessness is higher in Turkey compared to other countries. Addictive substances negatively affect the perceptions of the general health status of more than half of the homeless, especially in Italy. Although the phenomenon of homelessness, which is growing day by day in societies as a global threat, is triggered by similar factors, it is seen that the causes and results differ in the axis of factors such as culture, law, belief, social life, social problem, family relations at the local level. Low education level, alcohol and substance abuse, economic inadequacy, and problems related to family and social relations are common as homeless individuals' most basic problem areas. As a global problem, the issue of homelessness is an area that all societies should work on and produce common solutions.